G574(P) Rising trend in the incidence of congenital hyperinsulinism at district general hospital. (May 2019) - De Silva, PN; Muhammad, BJ; Skinner, A; Padidela, R; Yau, D
Abstract : Aims: Congenital hyperinsulinism (CHI) is a rare condition, which is estimated to affect 1 in 25 000 newborn babies. The incidence is much higher in consanguineous parents, possibly as frequently as one in every 2500 children. From July 2017 to July 2018, we have identified 6 cases of CHI in our neonatal unit; these patients are looked after in conjunction with a specialist tertiary endocrine team. We noted a rising incidence and explored if there were any common contributory factors that may have attributed to hyperinsulinism. Methods: We retrospectively reviewed the medical notes of the 6 cases. We considered factors such as gestation at birth, birth weight, ethnicity, consanguinity, presence or absence of gestational diabetes mellitus in all cases. We also looked at the insulin level and glucose load at diagnosis, whether they required treatment with diazoxide and if so the duration of treatment. Results: All 6 cases met the criteria for diagnosis with a glucose load of >10 mg/kg/min and a raised insulin level. All the babies were born to non-consanguinous parents and only one of the patient's mothers had gestational diabetes. 4 out of the 6 babies had IUGR (table 1 ) and most of the patients demonstrated a degree of perinatal stress. All the patients required treatment with diazoxide; 5 of the patients' treatment was discontinued after 3–6 months as the hyperinsulinism was transient. None of the patients had genetic tests done. Conclusion: We have identified an increasing incidence of congenital hyperinsulinism in our neonatal unit in the last year, the majority of which was transient. We have identified that the majority of babies had IUGR and demonstrated evidence of similar perinatal stress which are well recognised causes of transient CHI.